Making of Concentrates Protein Catfish and Its Application in Dumplings Crackers - Randi B.S. Salampessy; Resmi R. Siregar (Jurnal Perikanan dan Kelautan, 2012)
Crackers dumplings that much-loved public generally contains less protein, to increase the protein content and add flavor, the addition of Fish Protein Concentrate (FPC) is the right choice. This study aimed to determine the flow of the process of making protein concentrate catfish, crackers dumplings with the addition of FPC, and know the content of the proximate and microbiology. This study was conducted on March 1 until 14 April 2012, in a modern processing workshop, chemical and microbiological laboratories Fisheries Jakarta University.  This activity uses FPC processing equipment, cracker dumplings and analysis tool for chemical and microbiological testing. Materials used catfish, wheat flour, eggs, butter, and chemical analysis of chemical and microbiological testing. Work methods, beginning with the protein concentrate catfish, processing cracker dumplings with the addition of  protein concentrate catfish (0%, 2%, 4%). Then, determine the selected products, examined for chemical and microbiological quality. Data analysis method is descriptive quantitative and qualitative. The conclusion of this study are stage of making a protein concentrate catfish are : preparation, the destruction of the flesh, extraction, pressing, drying, and grinding and sieving . The process of making crackers dumpling with the addition of protein concentrate catfish  that mixing of materials, pressing, drying, and packaging. The best products based on hedonic test is crackers dumplings with 2% protein concentrate catfish (product B). The proximate test results are the moisture content of 16.75%, ash content 1.25%, 36% fat content and protein content 18.95%. The ALT test results of raw materials are1.7 x 104 col / gr and the product B’s 2.8 x 103 col / gr and bacteria E. Coli is negative. Keyword: concentrate protein, catfish, crackers, dumpling